Pengaruh Pendapatan Asli Daerah (Pad), Dana Perimbangan, Dan Sisa Lebih Pembiayaan Anggaran (Silpa) Terhadap Belanja Modal (Studi pada Pemerintah Kabupaten/Kota di Provinsi Jawa Tengah Periode 2013- 2015). - Hermawan, Rudi, Fauzan S.E, Ak, M.Si, Ak (2017)
This research aim to analyse influence of local genuine revenues (PAD), Local Own Sources Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK) and Budget Financing Surplus (SILPA) to the Capital Expenditure (BM). The independent variables are Local Own Source Revenue (PAD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK) and Budget Financing Surplus (SILPA). Meanwhile, the dependent variable is using Capital Expenditure (BM). The samples are 29 districts and 6 cities in Central Java Province and the research is a three-year periods in 2013-2015 fiscal years. The sample collection technique has been done by using saturation sampling. The government data is in the form of secondary data in the APBD Realization statement of Central Java Governance in 2013-2015. The analysis method has been done by using multiple linear regressions. The result of this research shows that (1) Local Own Source Revenue (PAD) has influence to the Capital Expenditure (BM), (2) Revenue Sharing Fund (DBH) has influence to the capital expenditure (BM), (3) General Allocation Fund (DAU) has influence to the capital expenditure, (4) Special Allocation Fund (DAK) has influence to the capital expenditure, (5) Budget Financing Surplus (SILPA) does not have any influence to the capital expenditure.